Control of Raw Material Inventory to Fulfill Consumer Demand for Refil Perfume at Fadil Perfume in Ogotua Village Toli-Toli Regency - Dandi; Farid; Umar (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2025)
This study aimed to analyse the control of raw materials inventory to meet consumers' demands for refill perfume at Fadil Parfum, using a quantitative research approach. The analysis method applied in this research was the Economic Order Quantity (EOQ) method. Based on the analysis conducted, the EOQ method provided more optimal and economical inventory control results for refill perfume raw materials at Fadil Parfum in Ogotua Village, North Dampal District, Tolitoli Regency, compared to the inventory policy previously implemented by the store. The EOQ method resulted in ordering larger quantities of raw materials with lower ordering frequency, which helped minimise the total ordering costs.